Beverage-Cans as a Source of Hydrogen - Analysis of Leaching Residues - Michalcová, Alena; Novák, Pavel; Msallamová, Šárka (Manufacturing Technology Journal, 2026)
Aluminium beverage-can are common material for secondary utilization. Their recycling is slightly com-plicated by presence of organic materials in them and lack of collection points (although the legislative in this case is rapidly changing to be more friendly). Another approach to deal with beverage-cans is using them as a source of hydrogen. In this manuscript, the evolution of hydrogen in 10 wt. % NaOH solution is described. The leaching residues were analysed in detail. Their chemical and phase composi-tion were measured, and the amount of trapped hydrogen was also analysed. The beverage-cans are usually composed of 3004 and 5182. The residues after leaching contained beside organic residues oxides and hydroxides in both cases of initial alloys. Surprisingly, the amount of hydrogen in leaching residues is almost negligible.
Keywords: Beverage-can; Aluminium leaching; Hydrogen evolution; NaOH; Aluminium